What drives EU banks' stock returns? Bank-level evidence using the dynamic dividend-discount model - Olli Castrén; Trevor Fitzpatrick; Matthias Sydow (European Central Bank (ECB), 2006)
We combine the dynamic dividend-discount model with an accounting-based vector autoregression framework that allows for a decomposition of EU banks' stock returns to cash-flow and expected return news components. The main findings are that while the bulk of the variability of EU banks' stock returns is due to cash flow shocks, the expected return shocks are relatively more important for larger than for smaller banks. Moroever, variables used in the literature as cash-flow proxies explain a higher share of the cash-flow component of the total excess returns for smaller than for larger EU banks. This suggests that large banks could be more prone to market wide news and events - that in the literature are associated with the expected return news component - as opposed to the bank-specific news, typically assumed to be incorporated in the cash-flow component.
Keywords: C33; G12; G21; 330; Bank stock return predictability; cash flow news; panel VAR estimation; return decomposition; Wertpapier; Börsenkurs; Bank; Cash Flow; VAR-Modell; Theorie; EU-Staaten